Mathematical modeling - Effective Technology for aeronautical equipment failure imitation - Моржов, В. И.; Єрмачков, Ю. А.; Моржова, Л. И. (Problems of Informatization and Control, 2012)
In the article, the issues of aeronautical equipment failure imitation are concerned in various modes of aircraft operation. It has been shown that aeronautical equipment failure imitation is reasonable to perform by means of Mathematical modeling. In the article, the results are given for modeling failure of aircraft’s gas-turbine engine